Second harmonic generation in dissipative metamaterials - Mukhametkarimov, Ye.S.; Kudyshev, Zh.; Davletov, A.E.; Gabitov, I.; Maimistov, A. (Recent Contributions to Physics, 2012)
In the regime of continious waves the second harmonic generation process in dissipative negative refraction-index metamaterials is considered. At small values of the phase mismatch the intensity distributions of both the fundamental and second harmonic waves are monotonic functions of coordinates. But if the phase mismatch reaches some critical value, the intensity distributions of the two waves undergo a transition from monotonic to oscillatory pattern. The influence of the losses in the medium on that critical value of the phase mismatch is numerically studied.